Helicobacter and gastric MALT lymphoma. (1st May 2002) - Stolte, M; Bayerdörffer, E; Morgner, A; Alpen, B; Wündisch, T; Thiede, C; Neubauer, A
Abstract : Helicobacter pylori infection is a pre-MALT lymphoma condition. H pylori eradication leads to complete remission in 80% of low grade stage E1 lymphomas, with a yearly recurrence rate of approximately 5%. The possibility for complete remission in high grade lymphomas needs to be investigated in prospective studies. In addition, the significance of persistent B cell monoclonality (stable disease? danger of relapse? regression of monoclonality?) needs to be investigated in follow up studies.